Acquired port-wine stain in an adult male: First reported case from India with review of literature - Shuchi Bansal; Vijay K Garg; Bhawna Wadhwa; Nita Khurana (Indian Journal of Dermatology, 2015)
Port-wine stains (PWSs) are congenital vascular lesions caused by progressive ectasia of blood vessels located in the vascular plexus of the dermis. Acquired PWSs develop later in life but are identical in morphology and histology to the congenital PWSs. Less than 75 cases of acquired PWSs have been reported in the published literature, of which there has not been a single report from India so far. Various factors have been proposed for its pathogenesis like trauma, actinic exposure, drugs, tumors, and herpes zoster infection. We report an acquired port-wine stain in a 41-year-old male. The causative factors, treatment, and previous reports of this uncommon entity have also been reviewed.